2004
DOI: 10.1037/1528-3542.4.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Decoding speech prosody: Do music lessons help?

Abstract: Three experiments revealed that music lessons promote sensitivity to emotions conveyed by speech prosody. After hearing semantically neutral utterances spoken with emotional (i.e., happy, sad, fearful, or angry) prosody, or tone sequences that mimicked the utterances' prosody, participants identified the emotion conveyed. In Experiment 1 (n ‫ס‬ 20), musically trained adults performed better than untrained adults. In Experiment 2 (n ‫ס‬ 56), musically trained adults outperformed untrained adults at identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
319
5
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(359 citation statements)
references
References 105 publications
23
319
5
12
Order By: Relevance
“…This is hardly surprising because an important component in music training is dealing with emotional meaning and expressiveness, which is likely to enhance the recognition of subtle emotional qualities in music. The advantage of music training is also consistent with the available evidence on the benefits of music training (e.g., Moreno et al, 2008;Schellenberg, 2004) and especially with studies reporting an improvement in the recognition of emotions (Thompson et al, 2004). However, there is also research that failed to find effects of musical expertise on the implicit emotional assessment of musical excerpts (Bigand et al, 2005), and our study was not designed to test the role of this factor (years of musical training were controlled a posteriori).…”
Section: Correlation With Music Trainingsupporting
confidence: 72%
See 1 more Smart Citation
“…This is hardly surprising because an important component in music training is dealing with emotional meaning and expressiveness, which is likely to enhance the recognition of subtle emotional qualities in music. The advantage of music training is also consistent with the available evidence on the benefits of music training (e.g., Moreno et al, 2008;Schellenberg, 2004) and especially with studies reporting an improvement in the recognition of emotions (Thompson et al, 2004). However, there is also research that failed to find effects of musical expertise on the implicit emotional assessment of musical excerpts (Bigand et al, 2005), and our study was not designed to test the role of this factor (years of musical training were controlled a posteriori).…”
Section: Correlation With Music Trainingsupporting
confidence: 72%
“…Based on the finding that musicians perform better than non-musicians in emotion recognition tasks (Thompson, Schellenberg, & Husain, 2004), we also investigated the correlation between years of music training of the participants (controlled a posteriori) with accuracy on a derived measure of accuracy.…”
Section: Emotion Recognition In Music Changes Across the Adult Life Spanmentioning
confidence: 99%
“…A number of studies have already reported a positive relationship between musical competence and the processing and imitation of a foreign accent (Schön et al, 2004;Thompson et al, 2004;Wong and Perrachione, 2007;Pastuszek-Lipinska, 2008;Milovanov, 2009;Nardo and Reiterer, 2009;Kraus and Chandrasekaran, 2010;Reiterer et al, 2011;Hu et al, 2012;Christiner, 2013). Musicians, that is to say individuals with increased musical ability, show an improved auditory working memory and remember speech streams for longer when compared to those without (Pastuszek-Lipinska, 2008;Nardo and Reiterer, 2009;Reiterer et al, 2011;Hu et al, 2012;Christiner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We then compared this to their ability to sing and their working memory skills. The aim was to go beyond previous L2 research which had, to this point, focussed mainly on music perception and its effect on the production and memorization of language (Schön et al, 2004;Thompson et al, 2004;Wong and Perrachione, 2007;Pastuszek-Lipinska, 2008;Milovanov, 2009;Kraus and Chandrasekaran, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Music training has been shown to enhance the ability to decode emotions conveyed by speech prosody (e.g., Nilsonne & Sundberg, 1985;Thompson, Schellenberg, & Husain, 2004). Indeed, emotions are also at the core of music.…”
mentioning
confidence: 99%